Green placemaking on the peripheral prairie following a natural disaster. Issue 1 (2nd January 2023) - Che, Deborah
Abstract: Peripheral areas have utilized placemaking and tourism to address their economic and demographic challenges. When a 2007 tornado destroyed 95% of peripheral Greensburg, Kansas, the city used the subsequent window of opportunity to implement tangible, strategic combined green placemaking and place-making that involved green/advanced technologies and tourism based on the green buildings. However, the technocratic green solutions and placemaking did not fully acknowledge the structural issues related to Greensburg's peripheral location such as increased transportation and housing construction costs that have hampered the city's recovery. For peripheral areas following a natural disaster, national and state government support for affordable housing and for linking these areas' unique assets and entrepreneurs to markets is required to compliment placemaking. Greensburg's green pedigree also needs to be translated in an ongoing, understandable way to sustainability tourists. For such post-disaster peripheral places, placemaking should not be viewed as a panacea and solely through an economic lens, but rather as part of a long-term strategy for revitalization and for contributing to increased resiliency, community pride, and a new sense of place.